Pengaruh Penambahan Daun Jeruk Nipis (Citrus Aurantifolia) terhadap Aktivitas Antioksidan Minuman Seduhan Daun Kumis Kucing (Orthosiphon Aristatus Bl. Miq.) - Bahria Ulfa; Khoirin Maghfiroh (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
The use of medicinal plants as herbal beverages has long been a part of Indonesian culture. However, the less preferred taste and aroma are obstacles to consumer acceptance. Cat's Whiskers leaves (Orthosiphon aristatus) are known to contain bioactive compounds that act as antioxidants, while Key Lime leaves (Citrus aurantifolia) have a fresh aroma and functional properties that can enhance flavor and health benefits. This study aims to evaluate the effect of adding Key Lime leaves (Citrus aurantifolia) on the chemical characteristics, sensory properties, and effectiveness of brewed Cat's Whiskers (Orthosiphon aristatus) leaf beverages.Five formulations with varying concentrations of Key Lime leaves (0%, 5%, 10%, 15%, and 20%) were tested based on the parameters of moisture content, ash content, pH, solubility, antioxidant activity, and organoleptic tests including color, aroma, taste, and texture. The results showed that the addition of Key Lime leaves significantly improved the chemical quality and sensory acceptability, with the best formulation obtained in treatment P4 (20% Key Lime leaves + 15g Cat's Whiskers), which provided an optimal balance between stability, nutritional content, and organoleptic quality. The addition of Key Lime leaves is recommended as an innovation in the development of functional herbal beverages based on Cat's Whiskers.